2014
DOI: 10.1177/1468087414560776
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of closely coupled pilot and main injections as a means to reduce combustion noise in a small-bore direct injection Diesel engine

Abstract: Various pilot-main injection strategies are investigated in a single-cylinder optical Diesel engine. It is observed that as the dwell between a single pilot and the main injection is decreased toward zero, combustion noise passes through a minimum, and a reduction of 3 dB is possible. The injection schedules employed in the engine are analyzed with a hydraulic injection analyzer to provide rate shapes for each of the dwells tested. Two distinct injection events are observed even at the shortest dwell tested, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 12 publications
(14 reference statements)
5
32
0
Order By: Relevance
“…In the present case, it is even shown that the application of a single main rate-shaped injection (mM strategy), obtained by means of injection fusion, can also give a better result than a pM injection schedule. Furthermore, the CN results plotted in Figure 10 are also in line with data on digital rate shaping injection schedules tested at moderate loads in Busch et al: 13 the minimum CN was achieved at DT = 140 ms and a reduction of 1.5 dB was detected compared to long DTs.…”
Section: Closely Coupled Pm Injections and Injection Fusionsupporting
confidence: 85%
“…In the present case, it is even shown that the application of a single main rate-shaped injection (mM strategy), obtained by means of injection fusion, can also give a better result than a pM injection schedule. Furthermore, the CN results plotted in Figure 10 are also in line with data on digital rate shaping injection schedules tested at moderate loads in Busch et al: 13 the minimum CN was achieved at DT = 140 ms and a reduction of 1.5 dB was detected compared to long DTs.…”
Section: Closely Coupled Pm Injections and Injection Fusionsupporting
confidence: 85%
“…The combustion process has been smoothened with the association of pilot injection in double-and triple-injection strategies. Introduction of pilot injection reduced the maximum PPR and help in reducing the engine noise [34]. Apart from that, the HHR peak for double and triple injection also reduced as compared to single injection.…”
Section: Response Characteristicsmentioning
confidence: 97%
“…Multiple fuel injection strategies have been proven to reduce the CI engine emission [32,33]. Essentially, introduction of pilot injection can help to reduce the engine noise and NO x emissions [34]. Main injection with fully open needle (rectangular shape) or boost-type shape will also reduce NO x emissions and post injection reduce the soot emissions [35,36].…”
Section: Prior Studiesmentioning
confidence: 99%
“…In positive displacement devices such as reciprocating internal combustion engines however, the interplay between thermal and acoustical phenomena is completely different due to their cyclic, unsteady operation, and to the fact that the process occurs in a closed fluid domain. Thus, even being merely direct, combustion noise can be generated by distinct causes within the same combustion process [36,37]. Moreover, the acoustic response can be different owing to the interference between the pressure waves and the chamber walls [38].…”
Section: Physics Of Combustion Noise Generationmentioning
confidence: 99%